Assessing the model of Wheelen and Hunger (2008) model of internal environmental scanning and its applications to the Small Medium Enterprise (SME) in Malaysia - Cheng, Wei Hin; Bohari, Abdul Manaf; Md Isa, Filzah; Mohd Maddin, Ardzmi (Society for Business Research Promotion, 2013)
The purposes of this study are to investigate whether SMEs in Malaysia do environmental scanning and levels of importance of internal environmental scanning factors to the SMEs.SME has contributed quite large percentage to the growth of Gross Domestic Product (GDP) in Malaysia.It is crucial for every company to analyze strengths and weaknesses of the internal and external environment to enable the business sustain and growth.Three hundred structured questionnaires were mailed to SMEs in the Northern states (Perlis, Kedah and Penang) and only 108 questionnaires were used in the statistical analysis.The results show that over 60% of the companies interviewed agreed that they perform environmental scanning.The factors of internal environmental scanning following the important level for the participants are finance, products, skill, values, communication, system, management style, asset, super-ordinate goals and belief.